Kontribusi Keterwakilan Perempuan di Legislatif dalam Indeks Pembangunan Gender (IDG) - Indra Kertati (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2019)
The Gender Empowerment Index (GDI) is a measure obtained from women's indicators in the legislature, professional women and women's income contribution. Of these three indicators, the position of women in the legislature is a massive inator that will only move once every 5 years. The regulation on political representation has been established since 2003 by setting a quota of 30%, but on the way up to 16 years the affirmative action has not been successful. The reason is the role of political parties is not optimal, female candidates are limited human resources and limited in the narrow nomination. The position of women's representation in the legislature contributes greatly in forming GDI. Women's contributions will be massive within 5 years. Therefore a strategic step is needed to collaborate between the power of political parties in promoting female candidates with political capital owned by women. Strong political parties have the opportunity to make this happen.